Considering a risk profile based on emergency department utilization in young people with eating disorders: Implications for early detection. Issue 9 (26th July 2021) - Redekopp, Carlie; Dimitropoulos, Gina; Patten, Scott; Kassam, Aliya
Abstract: Objective: While screening tools are available for the early identification of eating disorders, it may not be feasible to employ them in an emergency department (ED). Establishing a risk profile may improve the screening process. The purpose of this study was to investigate ED service utilization among patients with eating disorders and create a risk profile to help detect eating disorders at an earlier and more treatable stage. Method: We applied a concurrent mixed methods research design, however, only the quantitative findings will be presented. Our study involved a retrospective cohort analysis of administrative ED health data for patients ( n = 243) aged 12–24 years in an eating disorders program. Two control groups: (1) all‐cause ( n = 716), (2) and mental health ( n = 679) were included. Results: 68.7% of eating disorder patients were discharged from the ED without follow‐up being arranged. Comorbidities were recorded as the primary or secondary diagnosis, and patients presented with suicidality more frequently than controls ( χ = 31.2, p < .001). Patients accessed ED services five times more often than controls. Discussion: Despite eating disorder patients accessing the ED more frequently than controls, eating disorder diagnoses were not always assigned or documented. Our findings highlight the importance of enhanced eating disorder training for ED health care staff to better understand the risk profile, and the consideration of comorbidities and suicide risk when assessing patients to ensure early detection. Conclusion: As eating disorders are often undetected, more comprehensive training and access to screening tools may help improve detection, mitigate symptom progression, and enhance patient safety.